Library fever: lesbian memoir and the sexual politics of order. Issue 1 (2nd January 2023) - Nichols, Ben
ABSTRACT: Scholars across disciplines have recognised the symbolic and practical importance of information infrastructures in queer lives – from archives to the contemporary Internet. This essay builds on this work to argue that crucial to understanding this fact is what it says about the place of structure and order in queer history and theory. While these ideas have tended to be maligned in queer thought, and imagined primarily as manifestations of Foucauldian power, the approach taken here is to highlight their specifically queer affordances. The essay focuses on a range of high-profile lesbian memoirs from the U.S. that prominently thematise the place of libraries and information access in lesbian lives: anthologies of coming out stories, Audre Lorde's Zami and Alison Bechdel's Fun Home . Libraries in these texts are lifelines, workplaces and romantic scenes: they become imbued with lesbian meaning. But they are also complexes of standardisation, order and classification. The texts' attachments to ordered information systems and to specifically lesbian identities are at odds with queer thought's long-standing aversions to both classification and identity. But this essay takes this tension as the occasion to interrogate core assumptions of queer studies that place queer lives only in opposition to all structure and order.